Quantile regression and the gender wage gap: Is there a glass ceiling in the Turkish labor market? - Ezgi Kaya (Cardiff University, Cardiff Business School, 2017)
Recent studies from different countries suggest that the gender gap is not constant across the wage distribution and the average wage gap provides limited information on women's relative position in the labour market. Using micro level data from official statistics, this study explores the gender wage-gap in Turkey across the wage distribution. The quantile regression and counterfactual decomposition analysis results reveal three striking features of the Turkish labour market. The first is that the gender wage gap is more pronounced at the upper tail of the wage distribution, implying the existence of a glass ceiling effect for women in the Turkish labour market. The second is that, the glass ceiling effect in Turkey is not observed in the raw gender wage gap and only revealed after controlling for workers' labour market qualifications implying that women are better qualified and better educated than their male counterparts' at the upper tail of the wage distribution. The third finding is that despite the narrowing effect of the women's relative labour market qualifications, the glass ceiling effect in the Turkish labour market exists due to unequal treatment of men and women and the increasing labour market discrimination toward women as we move up the wage distribution.
Keywords: C21; J31; J71; 330; Gender wage gap; quantile regression; decomposition